Parvalbumin expression changes with retinal ganglion cell degeneration - Liu, Yuan; Cheng He, Rossana; Munguba, Gustavo C.; Lee, Richard K. (Frontiers in Neuroscience, 2023)
Background Glaucoma is one of the main causes of irreversible visual field loss and blindness worldwide. Vision loss in this multifactorial neurodegenerative disease results from progressive degeneration of retinal ganglion cells (RGCs) and their axons. Identifying molecular markers that can be measured objectively and quantitatively may provide essential insights into glaucoma diagnosis and enhance pathophysiology understanding. Methods The chronic, progressive DBA/2J glaucomatous mouse model of glaucoma and C57BL6/J optic nerve crush (ONC) mouse model were used in this study. Changes in PVALB expression with RGC and optic nerve degeneration were assessed via gene expression microarray analysis, quantitative real-time polymerase chain reaction (qRT-PCR), Western blot and immunohistochemistry. Results Microarray analysis of the retinal gene expression in the DBA/2J mice at different ages showed that the expression of PVALB was downregulated as the mice aged and developed glaucoma with retinal ganglion cell loss. Analysis of qRT-PCR results demonstrated PVALB at the mRNA level was reduced in the retinas and optic nerves of old DBA/2J mice and in those after ONC compared to baseline young DBA2/J mice. PVALB protein expression measured by Western blot was also significantly reduced signal in the retinas and optic nerves of old DBA/2J mice and those eyes with crushed nerves. Immunohistochemical staining results demonstrated that there were fewer PVALB-positive cells in the ganglion cell layer (GCL) of the retina and staining pattern changed in the optic nerve from old DBA/2J mice as well as in mice eyes following ONC. Conclusion PVALB is abundantly expressed both by RGCs’ soma in the retinas and RGCs’ axons in the optic nerves of C57BL/6J. Furthermore, the expression level of PVALB decreases with RGC degeneration in the glaucomatous DBA/2J mice and after ONC injury of C57BL6/6J, indicating that PVALB is a reliable RGC molecular marker that can be used to study retinal and optic nerve degeneration.